Perancangan Interior âHosanna Florist And Handycraftâ Di Mojokerto - Andereas Pandu Setiawan, Andreas Eka Saputra M (Intra, 2014)
Nowadays, people more realize about beauty. We can see it from every events which is held by people like birthday, wedding, thanksgiving, funeral, etc. Flowers are universal beauty.Â  Because of that, flowers can be an alternative to answer individual needs of beauty. âHosanna Florist and Handycraftâ is one of famous florist in Mojokerto. The most important thing from the designâs shop is for change peopleâs mind set from florist as a flower shop become the answer of the beautyâs need. This florist interior design shows a modern naturalism style. Naturalism is shown from a flowers garden which can be seen from insideâs shop. It can make customers become comfort and being one with nature.